2011
DOI: 10.1124/dmd.111.043018
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine A- and Tacrolimus-Mediated Inhibition of CYP3A4 and CYP3A5 In Vitro

Abstract: ABSTRACT:Cyclosporine A (CsA) and tacrolimus (Tac) are immunosuppressive drugs used in the majority of patients with solid organ transplants, generally in combination with a wide range of drugs. CsA and Tac seem not only to be substrates of CYP3A but have also been described as inhibitors of CYP3A. For CsA, in particular, inhibition of CYP3A has been suggested as the main mechanism of interactions seen clinically with various drugs. The aim of this study was to investigate the inhibitory effect and inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 38 publications
4
64
0
Order By: Relevance
“…All recipients were administered cyclosporine or tacrolimus and methylprednisolone, and some were administered mycophenolate mofetil or mizoribine as immunosuppressive therapy. It has been reported that cyclosporine and tacrolimus inhibit intestinal CYP3A activity mildly (Amundsen et al, 2012), although mycophenolic acid, mizoribine, and methylprednisolone do not inhibit or induce CYP3A (Konishi et al, 2004;Kagaya et al, 2008). Therefore, there is a possibility that cyclosporine and tacrolimus may have affected CYP3A activity in this study.…”
Section: Downloaded Frommentioning
confidence: 62%
“…All recipients were administered cyclosporine or tacrolimus and methylprednisolone, and some were administered mycophenolate mofetil or mizoribine as immunosuppressive therapy. It has been reported that cyclosporine and tacrolimus inhibit intestinal CYP3A activity mildly (Amundsen et al, 2012), although mycophenolic acid, mizoribine, and methylprednisolone do not inhibit or induce CYP3A (Konishi et al, 2004;Kagaya et al, 2008). Therefore, there is a possibility that cyclosporine and tacrolimus may have affected CYP3A activity in this study.…”
Section: Downloaded Frommentioning
confidence: 62%
“…As previously described with midazolam, a typical CYP3A4/5 substrate, this interaction is most likely a consequence of intestinal and hepatic CYP3A4 inhibition, which is also involved in the metabolism of cyclosporine, tacrolimus, and everolimus (1). From a practical point of view, the interaction between boceprevir and immunosuppressive therapy required an average dose reduction of 50% of the three immunosuppressive drugs that are CYP3A substrates.…”
Section: Discussionmentioning
confidence: 82%
“…Second, high concentration of FK506 showed an inhibited effect on CYP3A. It was reported that FK506 competitively inhibited CYP3A in human liver microsomes, showing inhibition constants (Ki) of 0.61 mM (Amundsen et al, 2012). Third, the reported concentration of FK506 used in a liver-microsome-based metabolism study of FK506 was 3 ng/ml (Egashira et al, 2004).…”
Section: Discussionmentioning
confidence: 99%